2022
DOI: 10.1177/00224294221081000
|View full text |Cite
|
Sign up to set email alerts
|

Mentoring Graduate Students in Music Education: A Mixed-Methods Phenomenological Study

Abstract: Mentoring is a critical element in the well-being, socialization, and professional identity development of graduate students. Yet in music education, little is known about the graduate student mentoring experience from the mentors’ perspective. Therefore, the purpose of this mixed-methods study was to examine music teacher educators’ perspectives on and experiences with graduate student mentoring. We used a concurrent nested approach to mixed-methods phenomenological research (QUAN + PHEN) with a survey of a n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…Ethnic music, in its continuous development has absorbed a lot of artistic achievements, but also absorbed different styles of beautiful music art, especially in the music creation techniques, emotional expression is unique. Literature [10], based on an example study, pointed out that the music counseling carried out by the music graduate student instructors includes assisting students in carrying out music practice, cultivating communication with others, and the basic workplace survival ability of a music career. Literature [11] explored samples of traditional music lyrics and found that moderate conventional music packaging lyrics can improve public recognition and acceptance, and also help to promote and pass on traditional music.…”
Section: Introductionmentioning
confidence: 99%
“…Ethnic music, in its continuous development has absorbed a lot of artistic achievements, but also absorbed different styles of beautiful music art, especially in the music creation techniques, emotional expression is unique. Literature [10], based on an example study, pointed out that the music counseling carried out by the music graduate student instructors includes assisting students in carrying out music practice, cultivating communication with others, and the basic workplace survival ability of a music career. Literature [11] explored samples of traditional music lyrics and found that moderate conventional music packaging lyrics can improve public recognition and acceptance, and also help to promote and pass on traditional music.…”
Section: Introductionmentioning
confidence: 99%
“…Although music education at this stage is the responsibility of ET, the collaboration and intervention of MT can improve the quality of generalist teachers' music activities (Barrett et al, 2020;Baum, 2017;Bautista & Ho, 2021;Bond et al, 2022;Ibbotson & See, 2021;Rajan, 2017). Welch (2020) argues that collaboration between specialists (who have expertise in music) and generalists (who have knowledge of their pupils) can enrich everyone.…”
Section: Introductionmentioning
confidence: 99%
“…There has been a growing interest in examining mentoring practices and relationships with PMTs in recent decades (Abramo & Campbell, 2019;Bond et al, 2023;Davis, 2017;Draves, 2008;Palmer, 2018;Pellegrino, 2015). For example, Palmer (2018) addressed the importance of mentors becoming familiar with student teachers' personalities, preparation, and musicianship prior to practicum placements in order to help establish positive relationships.…”
mentioning
confidence: 99%